DEVELOPMENT OF SCIENCE LITERACY TEST INSTRUMENT ON TEMPERATURE, HEAT AND EXPANSION MATERIALS AT SMP NEGERI 8 MEDAN - Pasaribu, Maruahal Nicholas; Hardinata, Aristo (Department of Science Education, 2025)
This study aims to determine the feasibility of a science literacy test instrument based on content validity, item validity, reliability, level of difficulty, discrimination power, and effectiveness of distractor options, as well as teacher responses to the developed test instrument. The research and development of this test instrument used the ADDIE model which consists of 5 stages, namely analyze, design, develop, implement, and evaluate. The study was conducted at SMP Negeri 8 Medan through 2 stages of product trials, namely small group trials with 10 test participants from grades VIII-9, and large group trials with 30 test participants from grades VIII-8. The results of content validity based on the assessment of 5 validators, 25 questions were declared valid and suitable for use. Based on the small group trial, 20 questions (80%) were declared suitable for use and 5 questions (20%) were not suitable for use. In the large group trial, the results of the item validity of 20 questions (100%) were declared valid. The reliability value of the instrument was 0.735 with a high reliability interpretation. Based on the level of difficulty, 20 questions (100%) were obtained with moderate criteria, based on the discrimination power, 6 questions (30%) were obtained with good criteria and 14 questions (70%) with sufficient criteria, based on the effectiveness of distractor options, 20 questions (100%) were obtained with very effective criteria. The teacher's response to the developed test instrument obtained an average value of 89.90% with very good criteria. Based on the results of the data analysis, 20 questions on the developed science literacy test instrument were feasible to use and could measure students' science literacy levels.